A handbook for EMC testing and measurement - Morgan, David 1948- (London, United Kingdom Institution of Engineering and Technology, 1994)
The book reviews developments in the following fields: electromagnetic compatibility; EMC standards; EMC testing; radiated emission testing; antennas; radiated susceptibility testing; measurement equipment; electromagnetic transient testing; and uncertainty analysis.
Electronic reproduction.
Keywords: Electromagnetic compatibility -- Testing -- Handbooks, manuals, etc; Electronic apparatus and appliances -- Handbooks, manuals, etc; Electronic books